Analisis Penggunaan Rekam Medis Elektronik Terhadap Kepuasan Petugas Kesehatan Di Rumah Sakit X - Muhlizardy Muhlizardy; Asti Nurhayati; Winda Azmi Meisari; Dyah Rochani (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of electronic medical records (EMR) in hospitals has become a primary focus in efforts to improve the efficiency and accuracy of healthcare services. This study aims to identify the relationship between EMR usage and the satisfaction level of healthcare workers at Hospital X. The research method employed is a quantitative study with an analytical approach and a cross-sectional design, involving 55 healthcare workers using total sampling techniques. Data were collected through questionnaires that measured EMR usage and healthcare worker satisfaction. Data analysis was conducted using the chi-square test. The analysis results show that 44 respondents (80%) categorized their EMR usage as good, and 42 respondents (76.4%) were categorized as satisfied with their work. The chi-square test results yielded a p-value of 0.000 (p<0.05), indicating a strong relationship between the use of electronic medical records and healthcare worker satisfaction at Hospital X, particularly in terms of ease of access to information and the reduction of errors in medical record-keeping. This study concludes that although EMR provides significant benefits for improving the quality of healthcare services, system improvements and adequate support are necessary to achieve optimal satisfaction among healthcare workers.